Docklaboratoriet: Vårt alternativa laboratorium som i Frihet Utvecklas där Frihet Finns. Om systrarna SannaMaria och Kari i Monika Fagerholms Diva - Österholm, Maria Margareta (Tidskrift för litteraturvetenskap, 2009)
Subversive femininity in Monika Fagerholm’s novel Diva Monika Fagerholm’s novel Diva (1998) is built on a playful web of intertextuality based on literature, film, music and real life stories. It discusses different ways of being a girl and how to write about girlhood. Using inventive language and storytelling of many sorts, Diva portrays a multitude of subversive femininities. This article tells the story of two of the characters in the book, the sisters SannaMaria and Kari, and how they gradually misinterpret and exaggerate concepts of girlhood to create a world of their own. In this imaginary world, the Doll laboratory as they call it, SannaMaria casts Kari in the role of an oracle destined to become a butterfly. I interpret the events in the laboratory as a means for them to experiment with and negotiate expectations of gender and talk about themselves in a different way. Unfortunately this is not a story with a happy end; Kari dies and then becomes a saint for the girls in the neighborhood. The novel uses her tragic demise to criticize and question a classical motif, the dead or dying beauty, in the same way as it investigates many other images of femininity.